Effects of evolving salt precipitation on the evaporation and temperature of sandy soil with a fixed groundwater table. Issue 3 (9th April 2021) - Li, Xinhu; Shi, Fengzhi
Abstract: The effects of salt precipitation on water and heat transport in soil have garnered considerable attention. However, salt precipitation growth on the soil surface and its influence on soil evaporation and temperature under a fixed groundwater table are not well understood. Therefore, the objective of this study was to investigate the impact of the evolution of salt precipitation on evaporation and temperature in sandy soils with a fixed groundwater table depth (20 cm). The laboratory experiment consisted of two treatments for sand columns: one with fresh groundwater, and the other with saline groundwater. Regions with salt precipitates expanded laterally and vertically whereby a salt crust was formed that disconnected from the soil. The lateral growth of salt precipitation had a minor impact on evaporation as the soil remained wet, while mostly being covered by the salt crust. However, the elevated salt crust caused a sharp decrease (>60%) in the evaporation rate. Therefore, a new stage of saline soil evaporation was determined; the evaporation rate was further reduced by the elevated salt crust. Moreover, the soil profile temperature decreased when the soil was covered by the salt crust, which is likely attributable to the increased albedo and the formation of a layer of air owing to the elevated salt crust. Therefore, we suggest that the upward growth of salt precipitation should be comprehensively studied because it can cause significant reductions in evaporation rates and soil temperature.